Calidad de vida relacionada con la salud en Medellín y su área metropolitana, con aplicación del SF-36 (2014)
ABSTRACT: Health-related quality of life (qol) is the component which refers to the perception people have of their ability to lead a useful life and to develop their potential and, especially, of their overall health and the impact of disease and treatments on it. In order to evaluate the qol diverse scales were created. One of the most used of these is the SF-36, with which useful population-based reference values have been estimated in clinical and population-based research, in order to monitor the qol over time, among other uses. In Colombia these values are yet to be calculated. Objective: to obtain approximate qolvalues using the SF-36 Health Questionnaire in Medellín and its metropolitan area. Methodology: integrative quantitative study using data taken from 18 different pieces of research which used the Colombian version of the SF-36. Results: 54.4% of the respondents were male, who scored higher than women in all dimensions of qol. Scores ranged between 64.1 (sd: 22.5) in Mental Health and 40.8 (sd: 35.5) in Physical Performance. As age increases the score falls in the majority of categories, except in Social Function and Mental Health. Conclusion: the estimated values in these populations are less in all dimensions of qol than those from Mexico (except General Health), the United States and Canada, and are available for use in the evaluation of collective interventions, the follow-up for treatments given to patients and for national and international comparisons.